Synergic effect of metakaolin and groundnut shell ash on the behavior of fly ash-based self-compacting geopolymer concrete - Bheel, N. (Elsevier Ltd, 2021)
The sustainable self-compacting geopolymer concrete (SCGC) production is an eco-efficient concrete with a lower carbon footprint than conventional concrete. This experimental work was performed on the fly ash based SCGC mixtures which blended metakaolin and groundnut shell ash individually and combined them into 5â20 with an increment of 5 as replacement of fly ash in the mixtures. The main theme of this research work is to determine the fresh properties in terms of filling ability (slump flow, V-Funnel and T50 flow) and passing ability (J-Ring and L-box) tests and hardened properties in terms of compressive, splitting tensile and flexural strengths, and water permeability of the SCGC mixture. However, a total of 260 concrete specimens were made and tested at 28 days. The outcomes of this research work revealed that the addition of metakaolin and groundnut shell ash separate and combined as partial replacement of fly ash in the SCGC mixtures that causes a reduction in the workability, while the hardened properties of SCGC are significantly enhanced by using metakaolin and groundnut shell ash individually and combined up to 10 by the weight of fly ash. Moreover, the compressive, splitting tensile and flexural strengths of SCGC were measured as 56.42 MPa, 4.68 MPa and 5.12 MPa for the mix contained 5 of groundnut shell ash and metakaolin together at 28 days, respectively. Furthermore, the water penetration depth declined as the extent of metakaolin and groundnut shell ash as replacement of fly ash separate and combined rises in the mixtures. Â© 2021 Elsevier Ltd